Analisis Determinan Brand dan Celebrity Endorser Pada Keputusan Pembelian Konsumen di Outlet Rabbani Kota Jambi - Fathuddin Abdi (Indonesian Journal of Islamic Economics and Business, 2018)
The purpose of this study was to determine how much influence Celebrity Endorser and Brand Image have on purchasing decisions for rabbani products at Rabbani Outlet in Jambi City. This type of research is quantitative research. Data collection is done by means of a questionnaire (questionnaire) documentation and interviews. The sample taken in this study amounted to 100 people. The data analysis technique used is the validity test, reliability test, multiple linear regression, T test, F test and analysis of the coefficient of determination with the least squares equation and hypothesis testing using the F test, T test. The study was conducted with multiple linear regression equations for the influence of Celebrity Endorser. and Brand Image on the decision to buy rabbani products at Rabbani Outlet in Jambi City is Y = 0.221 X1 + 0.407X2 + e. Celebrity Endorse has a significant effect on consumer purchasing decisions because the value of tcount> ttable or 2.205> 1.984 and the resulting significant value is 0.030 more than 0.05. Brand Image has a significant effect on consumer purchasing decisions because the value of tcount> ttable or 4.055> 1.984 and the resulting significant value 0.000 is less than 0.05. The value of the coefficient of determination is 0.313 or equal to 31.3%. This means that the ability of the dependent variable (consumer purchasing decisions) can be explained by 31.3% by the independent variable (Celebrity Endorser and Brand Image) and the remaining 68.7% is influenced by other factors.